Characteristics, outcomes, and predictors of mortality at 3 months and 1 year in patients hospitalized for acute heart failure - Harjola, Veli-Pekka; Follath, Ferenc; Nieminen, Markku S.; Brutsaert, Dirk; Dickstein, Kenneth; Drexler, Helmut; Hochadel, Matthias; Komajda, Michel; Lopez-Sendon, Jose L.; Ponikowski, Piotr; Tavazzi, Luigi (European journal of heart failure, 2010)
Aims Acute heart failure (AHF) has a poor prognosis. We evaluated 3- and 12-month mortality in different clinical classes of AHF patients from 30 European countries who were included in the EuroHeart Failure Survey (EHFS) II. Methods and results Follow-up data were available for 2981 AHF patients, of these 62% had a history of chronic HF. One-year mortality after discharge was lower in patients with de novo AHF when compared with acutely decompensated chronic HF (ADCHF), 16.4 vs. 23.2% (P < 0.001). Cardiogenic shock conferred the highest cumulative 1-year mortality (52.9%) as a result of in-hospital mortality of 39.3%. Long-term prognosis in decompensated AHF was also dismal. Hypertensive HF was associated with the lowest mortality (13.7% at 1 year). Age, prior myocardial infarction, creatinine level, and low plasma sodium were independently associated with mortality during the whole follow-up period. Diabetes, anaemia, and history of chronic HF were associated with worse and hypertension with better long-term survival. History of cerebrovascular disease was associated with worse short-term outcome. Conclusion Early and late mortality differ between de novo AHF and ADCHF and between clinical classes of AHF. EHFS II identifies clinical risk markers and demonstrates the importance of a thorough characterization of AHF populations according to history and clinical presentation.
First published: 15 February 2010
Gesehen am 08.03.2023